Steps of perfection : exorcistic performers and Chinese religion in twentieth-century Taiwan - Sutton, Donald S. (Harvard East Asian monographs, 2003)
"One part of Taiwan's flourishing religious culture is the elaborate, colorful, and noisy procession of local gods accompanied by troupes of musicians and dancers. Among them are groups of performers with wild, outlandish painted faces portraying underworld generals who serve the gods and punish the living. Through their performances, these troupes claim to exorcise harmful forces from the community." "In conducting fieldwork among these troupes, the author confronted the question of making sense of their claims to a long history when all evidence indicated that the troupes had been insignificant until the 1970s and of their assertions of devotion to an accurate transmission of tradition given the diversity of performances. By concentrating on the stylistic variations in performances, he explains the troupes as organizations shaped by the "market forces" of supply and demand in the culture of religious festivals. By focusing on performances as the nexus of market and art, he shows how bodily performance is the site where religious statements are made and the power of the gods made visible."--Jacket